2017
DOI: 10.1007/s10719-017-9763-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of ganglioside DSGb5 expression in renal cell carcinoma

Abstract: Disialosyl globopentaosylceramide (DSGb5) is a ganglioside originally isolated from tissue extracts of renal cell carcinoma (RCC) with metastasis. Previous in vitro experiments have suggested that DSGb5 promotes metastasis by enhancing the migration of RCC cells and downregulating NK cell cytotoxicity against RCC cells. In this study, we investigated the clinicopathological significance of DSGb5 expression in RCC and outcomes of RCC patients. A total of 156 RCC patients who underwent surgical treatments at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Disialosyl globopentaosylceramide (DSGb5), is a ganglioside originally isolated from tissue extracts of RCC, and higher expression of DSGb5 is associated with lower recurrence-free survival in RCC 34 . DSGb5 expressed on RCC cells binding to sialic acid-binding lg-like lectin 7 (Siglec-7) on NK cells, which leads to inhibition of NK cell cytotoxicity 35 .…”
Section: (Iii) Tumor-associated Gangliosidesmentioning
confidence: 99%
“…Disialosyl globopentaosylceramide (DSGb5), is a ganglioside originally isolated from tissue extracts of RCC, and higher expression of DSGb5 is associated with lower recurrence-free survival in RCC 34 . DSGb5 expressed on RCC cells binding to sialic acid-binding lg-like lectin 7 (Siglec-7) on NK cells, which leads to inhibition of NK cell cytotoxicity 35 .…”
Section: (Iii) Tumor-associated Gangliosidesmentioning
confidence: 99%
“…Disialosyl globopentaosylceramide (DSGb5) is a dominant ganglioside isolated from RCC tissues [ 70 ] which binds to sialic acid-binding Ig-like lectin-7 (Siglec-7) expressed on natural killer (NK) cells, thereby inhibiting NK-cell cytotoxicity [ 71 ]. Higher DSGb5 expression exhibits greater migration potential in ACHN RCC cells and is correlated with metastasis in RCC patients [ 71 , 72 ]. Other gangliosides, such as GalNAc disialosyl lactotetraosylceramide [ 73 ] and monosialosyl galactosylgloboside (MSGG) [ 74 , 75 ], bring a higher risk of metastasis; however, the exact mechanisms are still not thoroughly investigated.…”
Section: Glycosphingolipids In Renal Cancermentioning
confidence: 99%
“…Primary RCC with expression of MSGb5 or GalNAcDSLc4 had a high risk of metastasis based on immunostaining in fresh-frozen sections of RCC tissue (Saito et al 1997;Maruyama et al 2007). DSGb5 expression was associated with microvascular invasion in paraffinembedded RCC tissues, and patients with high DSGb5 expression showed significantly lower recurrence-free survival rates (Itoh et al 2017). From the results of in vitro experiments using small interfering RNA (siRNA) transfectant for DSGb5 synthase gene, it was found that DSGb5 expressed in RCC cells inhibits the cytotoxicity of natural killer (NK) cells through interactions between sialic acidbinding immunoglobulin-like lectin-7 (Siglec-7) on NK cells and DSGb5 on RCC cells (Ito et al 2001a;Kawasaki et al 2010).…”
Section: Introductionmentioning
confidence: 95%